Teaching doctors how to teach. Issue 1 (1st December 2022) - Taylor, Charles Frederick Collins; Border, Scott
Abstract : Doctors are required to actively participate in the training and teaching of their colleagues and therefore must be competent at teaching others. However, opportunities to develop these required teaching skills are lacking in the current medical curricula. Consequentially, trainees are forced to look beyond the restraints of their standard curriculum. Near-peer teaching (NPT) appears to provide a fitting solution to the current lack of teacher training in medical education. NPT demonstrates well-documented benefits to the teacher, learner and faculty and is supported by several well-established pedagogical theories. Considering the requirement of future doctors to act as teachers and the importance of these skills, it may be appropriate to recommend that NPT no longer acts as a supplement to medical education, but rather as a core feature so that it may address the often ignored and neglected curricula component of teaching skills.